Religious Humanism Above Algorithms: Transforming Educators Through a Holistic Paradigm and Exemplary Ethics - Al Hakim, Hamka; Supriyanto Abdi (Universitas Muhammadiyah Surakarta, 2026)
The integration of artificial intelligence (AI) in education not only brings technological changes, but also affects the epistemological and normative meaning of education. Behind the narrative of efficiency and data-driven personalization, AI has the potential to give birth to algorithmic reductionism that simplifies education and obscures the ethical and humanistic dimensions of learning. This article aims to critically examine the integration of AI in education through the perspective of religious humanism, by placing educators as the main pedagogical and ethical subjects through a holistic paradigm and exemplary ethics. This research uses a qualitative approach with a critical-conceptual literature review design of reputable international and national scientific literature that discusses AI in education, humanism, hidden curriculum, educator professional identity, and multiculturalism. The results of the study show that the dominance of algorithmic logic in education risks eroding the essence of education if it is not accompanied by strengthening the role of educators as value bearers, ethical examples, and mediators of diversity. This article asserts that meaningful AI integration must subordinate technology to the goal of humanity, with religious humanism as the foundation of educator transformation. The contribution of this study is conceptual and paradigmatic, offering a reflective framework for policy development, pedagogical practice, and educational research direction in the era of artificial intelligence